The Value of By-Catch: Can We Use Commercial Species Stock Assessment Cruises for the Study of Non-Target Species? The Case of Sponges - Laura Schejter; Esteban Gaitán; Mariela Pavón Novarin (Biology and Life Sciences Forum)
The contribution of sponges to benthic communities in three areas of the Argentine continental shelf and slope (North, Central and South), between 34° and 55° S and between 47 and 551 m, is presented here. Sponges were recorded as components of the invertebrate by-catch in 51% of the studied sites (133 hauls). On average, sponges constituted 18.01% of the benthic community (47.91 kg/mn2, in terms of density), reaching more than 90% of the by-catch and more than 500 kg/mn2 at some particular sites. A total of 34 sponge taxa were recorded. Tedania spp., Clathria (C.) microxa and Callyspongidae (Siphonochalina fortis + Callyspongia sp.) were the only taxa shared among the three sampled areas. Sixty percent (60%) of the sponge species were recorded only at one or two sites.